ANALYSIS OF STUDENT DIFFICULTIES IN SOLVE QUESTIONS PROBLEM SOLVING ABILITY BASED ON DYNAMIC FLUID MATERIALS IN SMA/MA MEDAN CITY - Arliza, Winda; Warty, Yuni (IPER (Indonesian Physics Education Research), 2024)
This research aims to determine the level of students' problem solving abilities and to determine the difficulties experienced by students in solving problems based on problem solving abilities in dynamic fluid material. This type of research is qualitative research. The data sampling technique in this research uses a purposive sampling technique. The subjects in this research were class The results obtained show that SMA Negeri 8 Medan, MAN 1 Medan, SMA Private Dwiwarna, and Private SMA Islam Azizi have a good level of problem solving ability according to Heller at the problem focusing stage. the stage of describing the problem was categorized as sufficient, the stage of preparing a plan was categorized as sufficient, the stage of implementing the plan was categorized as inadequate, and the evaluating stage was categorized as insufficient. As for the difficulties experienced by students in solving problems based on problem-solving abilities in dynamic fluid material, namely Public High School 8 got 47.9%, MAN 1 Medan school got 45.9%, Dwiwarna Private High School got 42.0%, and Azizi Islamic Private High School got 37.8%.